Assessing Depression Levels Among University Students in Selangor, Malaysia: A Post-COVID-19 Analysis of Prevalence and Gender Differences - Radin Ahmad Taufik Salikin Izaddin; Akmaliza Abdullah; Muhammad Sobri Faisal; Radin Mohd Akhmal Izaddin; Afifah Hamdan; Ahmad Syukran Baharuddin (RSIS International, 2026)
Tier 2 (Indexed by WOS/Scopus/ERA)